Roles and Responsibilities of Notaries in the Establishment of Limited Liability Companies After the Implementation of Law No. 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law No. 2 of 2022 concerning Job Creation - Setyawan, Rony (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
This research aims to analyze: 1) Provisions for establishing a Limited Liability Company according to Law No. 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law No. 2 of 2022 concerning Job Creation. 2) The role and responsibilities of a notary in establishing a Limited Liability Company in connection with the enactment of Law No. 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law No. 2 of 2022 concerning Job Creation. This type of research is normative legal research. The approach method in this research is the statutory approach. This type of data uses secondary data obtained from literature studies. The analysis in this research is prescriptive. The research results concluded: 1) Provisions for the establishment of a Limited Liability Company according to Law No. 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law No. 2 of 2022 concerning Job Creation, namely that the Law Maker differentiates the Establishment of a Limited Liability Company established by 2 (two) people or more with an Individual Limited Liability Company, but both types of Limited Liability Company must both have legal entity status. The difference is, a Limited Liability Company established by two or more people must be carried out with a notarial deed made in Indonesian. Meanwhile, an Individual Limited Liability Company is established based on a Statement of Establishment made in Indonesian. 2) The role of a notary in establishing a Limited Liability Company in connection with the enactment of Law No. 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law No. 2 of 2022 concerning Job Creation, namely making an authentic Deed in accordance with Article 109 of Law No. 6 of 2023 concerning Determination Government Regulation in Lieu of Law No. 2 of 2022 concerning Job Creation which states that a Company is established by 2 (two) or more people with a notarial deed made in Indonesian. The deed created as the basis for the formation of the PT is known as the Deed of Establishment. The responsibility of a notary begins when the deed of establishment is drawn up before a notary which includes, among other things, the formulation of the aims and objectives of the company, therefore the notary is required to be as thorough as possible regarding the matters contained in the Deed of Establishment. The notary is fully responsible for the data entered and the notary is ready to accept all forms of sanctions if it is proven that the notary has violated statutory provisions.